Evaluation of the Level of Innovation of Enterprises: Joint Application of Technology Readiness Level and Life Cycle Assessment - Aleksandra KUMOR-SULERZ; Bożena KACZMARSKA; Magdalena RYBACZEWSKA-BŁAŻEJOWSKA (Communications of International Proceedings, 2021)
The article presents an original method of assessing the level of innovation of enterprises, using the fruit and vegetable processing plant as an example. The developed method, based upon the assumptions of the Technology Readiness Level (TRL) and Life Cycle Assessment (LCA), is a new approach to the assessment of the level of innovation of enterprises. It enables not only a multi-criteria evaluation of the current level of innovation and eco-innovation of enterprises, but also an indication of possible directions of actions aimed at increasing the levels in question. The research conducted for the fruit and vegetable processing plant showed that it has a medium level of innovation with the dominance of technological innovation. The company's lack of sustainability indicates a shortage of internal growth drivers. Therefore, the basic change introduced by the company should be the development of an intellectual innovation, which in the future will result in the implementation of its own innovative and eco-innovative solutions.
Keywords: Innovation; enterprise; Life Cycle Assessment (LCA); Technology Readiness Level (TRL)